Bilateral Angle Narrowing and Acute Myopia Induced by Indapamide: A Case Report - Ana Catarina Pedrosa; Joana Rodrigues Araújo; João Paulo Macedo; Sérgio Estrela Silva; António Melo; Fernando Falcão-Reis (Case Reports in Ophthalmological Medicine)
Purpose. To describe a clinical case of indapamide induced bilateral angle narrowing and acute myopia. Materials and Methods. Clinical case report. Results. A 37-year-old Caucasian emmetropic man presented to the Emergency Department with complaints of acute-onset bilateral blurry vision, nine days after starting treatment for arterial hypertension with a combination of indapamide and amlodipine. Clinical examination revealed the presence of myopia and appositional closure of the anterior chamber angle. Ultrasound biomicroscopy and mode B ultrasonography disclosed bilateral ciliochoroidal effusion with anterior rotation of the ciliary body and iridocorneal angle narrowing. After intraocular pressure control with brimonidine and timolol, and replacement of indapamide/amlodipine by amlodipine only, the patient was discharged. Complete resolution of the clinical manifestations was observed after three weeks, with no sequelae. Conclusions. Indapamide may cause acute myopia and angle closure secondary to ciliochoroidal effusion that are fully reversible after drug withdrawal, as long as timely diagnosis is established. Therefore, indapamide, as well as other sulfonamide-derived drugs, must always be considered in the differential diagnosis of acute myopia and angle closure.